PEMANFAATAN DIGITAL MARKETING DALAM UPAYA PEMASARAN D’YURA KITCHEN - Deisya Maulida Al Hamid; Nelson Rumui; Syukron Anas (Politeknik Negeri Sriwijaya, 2023)
For MSME players, the most appropriate choice to increase revenue and develop their business is to do digital marketing by utilizing technological developments and social media. Unfortunately, not all business owners know how to do effective marketing in order to reach potential customers, including D'YuRa Kitchen. D'YuRa Kitchen is one of the MSMEs in Fakfak Regency that operates online in the culinary field. Currently, D'YuRa Kitchen business actors are still doing conventional online marketing, namely by posting through social media such as Facebook, Twitter, Instagram, and WhatsApp so that D'YuRa Kitchen cannot compete with other similar business actors. Digital marketing is an online marketing method that utilizes the sophistication of internet algorithms in recording the habits of internet users, making it easier for businesses to target potential customers. In the midst of competition from online business actors today, digital marketing is the right choice so that business actors can easily market their businesses effectively. The community service activity carried out by the team is to assist D'Yura Kitchens in conducting digital marketing of the products sold by D'Yura. Digital Marketing has proven to be able to boost the number of product sales and revenue of D'YuRa Kitchen in a short time.